PENGARUH INTENSITAS KOMUNIKASI ORANG TUA DAN SELF DISCLOSURE TERHADAP OVERSHARING OLEH GENERASI Z DI INSTAGRAM - Fajru Akbari Putra Sinik, Fikri; Noor Rakhmad, wiwid; Naryoso, Agus (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The oversharing behavior of Generation Z on Instagram is influenced by the lack of communication intensity between parents and children, which leads to inadequate supervision and guidance in social media use. As a result, Generation Z tends to seek social validation through oversharing, blurring the boundaries of privacy due to excessive self-disclosure. This study aims to determine the influence of parental communication intensity and self-disclosure on oversharing on Instagram, using an explanatory method and a non-probability sampling technique involving 100 respondents. Based on social penetration theory and family relationship schema, the results of the simple linear regression hypothesis test show that parental communication intensity is inversely related to oversharing, while self-disclosure has a positive relationship with oversharing. The significance value obtained is 0.000.